Effects of Pandemics on Migrant Communities: Analysis of Existing Sources - Otieno, Mollo Kenneth (Religions, 2021)
Gender, religion, and migration are perplexing issues, especially in this era of the COVID-19 pandemic in which gendered and religious dynamics are emerging within migrant communities across the world. The relations between these three concepts are explored within this bleak time that has exposed previously neglected dynamics present in migrant communities living in distant host countries in Asia, Europe, and the United States of America. In this paper, we discuss the intricacies within religion and gender among migrant communities and the gendered impacts that COVID-19 has had on the aforementioned migrant communities. Through a secondary desk review analysis of the diverse emerging literature, we show that there are gendered implications of the pandemic measures taken by governments as migrant communities occupy unique translocalities. Overall, the intersection of religion, gender, and migration underscores religion reproducing gender roles among the migrants. The reproduction of gender in religious institutions disadvantage women amidst the COVID-19 pandemic. The analysis confirmed the trivial fact that migrant women continue to suffer disproportionately due to increased unemployment and disease burden coupled with religious practices that continue to advance the upward mobility of male migrants. There is a need to recast the place of migrant women in this era, and lastly, religion plays a renewed role among migrant communities especially for women who have enhanced their social positions and organizational skills through it.